Terapi Relaksasi Otot Untuk Dysmenorrhea - Dwi Kustriyanti; B Boediarsih (Prosiding University Research Colloquium, 2018)
Dysmenorrhea refers to painful menstruation which appears in the luteal phase that could affect productivity and quality of life, while dysmenorrhea in adolescents can reduce the concentration of learning. Muscle relaxation therapy is a non-pharmacological treatment that is effective, efficient and simple therapy as an treatment of dysmenorrhea. This study was to determine whether the muscle relaxation therapy reduces for dysmenorrhea in adolescents. This study was conducted in May until September 2017 at Karya Husada Science Health College . This design was true experimental with randomized pretest posttest design. Dysmenorrhea screening using ACOG diagnostic criteria, in 207 female students to determine the prevalence of dysmenorrhea and it’s symptoms was recorded in the diary records symptom. Students with dysmenorrhea were divided into a control group (n=30) and an experimental group (n=30). Students in control group received deep breathing relaxation therapy and those in experimental group received muscle relaxation therapy. The intensity of pain, blood pressure, respiration and pulse were measured 15 minutes before being given treatment and would be measured again at 15 minutes after giving the treatment during menstrual pain. Instruments used Numerical Rating Scale. Result: Pain intensity before and after intervention in intervention and control group were 5,53 ± 1,167 vs 4,17 ± 1,053, P = 0,000 and 4,47 ± 1,358 vs 3,87 ± 1,96, P = 0,000 . Test paired t-test and Wilcoxon test to see changes in systolic, diastolic and respiratory pressure changes of pulse before and after relaxation. Comparison of the effects of muscle relaxation and deep breathing relaxation with P <0.05 (0.002) with Mann Whitney test. Muscle relaxation therapy was effective in reducing the intensity of menstrual pain or dysmenorrhea in adolescents.